Peran Manajerial Kepala Sekolah dalam Meningkatkan Kinerja Guru di Kabupaten Karawang: Penelitian - Masduki, Masduki; Rahmawati, Desi; Mestika, Gelar Gelora; Soraya, Evitha (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyse the role of principal managerial strengthening in improving teacher performance in Karawang Regency. Using a qualitative descriptive approach through literature review and managerial training results, this study assesses the effectiveness of leadership strategies such as vision building, open communication, and teacher empowerment. The results show that continuous managerial training improves the competence of school principals in program planning, academic supervision, and the use of learning technology. The impact is seen in improved teacher performance and student learning outcomes. However, limited resources and technological adaptation remain challenges. This study emphasizes that transformational leadership and sustainable management are key to building a collaborative culture and producing professional teachers in the modern education era.